Adaptive immune system in pulmonary sarcoidosis—Comparison of peripheral and alveolar biomarkers. (7th July 2021) - d'Alessandro, Miriana; Bergantini, Laura; Cameli, Paolo; Mezzasalma, Fabrizio; Refini, Rosa Metella; Pieroni, Maria; Sestini, Piersante; Bargagli, Elena
Abstract: Sarcoidosis is a multi-systemic granulomatous disease of unknown origin. Recent research has focused upon the role of autoimmunity in its development and progression. This study aimed to determine and define the disturbance and distribution of T and B cell subsets in the alveolar and peripheral compartments. Thirteen patients were selected for the study [median age, interquartile range (IQR) = 57 years (48–59); 23% were male]. Twelve healthy controls [median age, IQR = 53 years (52–65); 16% male] were also enrolled into the study. Cellular and cytokine patterns were measured using the cytofluorimetric approach. Peripheral CD8 percentages were higher in sarcoidosis patients (SP) than healthy controls (HC) ( p = 0.0293), while CD4 percentages were lower ( p = 0.0305). SP showed low bronchoalveolar lavage (BAL) percentages of CD19 ( p = 0.0004) and CD8 ( p = 0.0035), while CD19 + CD5 + CD27 − percentages were higher ( p = 0.0213); the same was found for CD4 ( p = 0.0396), follicular regulatory T cells (Treg ) ( p = 0.0078) and Treg ( p  < 0.0001) cells. Low T helper type 17 (Th17) percentages were observed in BAL ( p = 0.0063) of SP. Peripheral CD4 + C-X-C chemokine receptor (CXCR)5 + CD45RA − ) percentages and follicular T helper cells (Tfh)-like Th1 (Tfh1) percentages ( p = 0.0493 and p = 0.0305, respectively) were higher in the SP than HC. Tfh1 percentages and Tfh-like Th2 percentages were lower in BAL than in peripheral blood ( p = 0.0370 and p = 0.0078, respectively), while CD4 + C-X-C motif CXCR5 + CD45RA − percentages were higher ( p = 0.0011). This is the first study, to our knowledge, to demonstrate a link between an imbalance in circulating and alveolar Tfh cells, especially CCR4-, CXCR3- and CXCR5-expressing Tfh subsets in the development of sarcoidosis. These findings raise questions about the pathogenesis of sarcoidosis and may provide new directions for future clinical studies and treatment strategies. Graphical Abstract: